Rachel Stern: capstone - Stern, Rachel, artist (Colorado State University. Libraries, 2017)
The artist's statement: Design is everywhere to the point that is has become a necessity in any project, company, or experience. Yet, so often I find that design is treated as an afterthought. When I approach design I see it as more than just a pretty logo or nice colors quickly thrown on top to make something appealing, for the purpose of design is so much more. Design creates emotion, makes a mark on the world, and most importantly it tells a story. These aspects is what create a relationship with the user and ultimately it creates a brand people can trust. We as humans care more about our relationships with our friends and family than our things. I strive to create a strong brand so whatever I design can feel a part of the family. It is that mindset that I always focus on in every project. No matter what is being designed, what makes it unique or relatable must be the focus. I see it as my job to encapsulate the emotion and the values and translate that into the design. I focus heavily on color and movement to convey and amplify that feeling to anyone who will interact with the piece. I focus on simplicity of the design first to create a feel that is easy to take in from the viewer's point of view and then tell the story in the details to keep their attention. Relationships mean so much to us, and it is hard to create a relationship with something that has no story. Building these aspects creates loyalty and attachment from the viewer to the brand and that is what matters most to me. I became a designer to bring beauty to our world, but I also want to bring meaning to it. Too often do I buy something from the store that brings me little joy because it is just an object. However, when something has personality, meaning and a reputation, I am the first to share with those I care about. I have always loved telling stories, and in design I help others tell theirs.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: design; graphic design